( N = 1 ∑ 1 0 2 4 ⌊ lo g 2 N ⌋ ) m o d 1 0 0 0 = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Great job! Can you generalize for the sum N = 1 ∑ 2 M ⌊ lo g 2 N ⌋ for positive integer M ?
Here's the generalization:
As we did in the original solution, using the properties of logarithm and floor function, we can write the generalized sum as,
S = N = 1 ∑ 2 M ⌊ lo g 2 N ⌋ = ⎝ ⎜ ⎛ k = 0 ∑ M − 1 j = 2 k ∑ 2 k + 1 − 1 k ⎠ ⎟ ⎞ + ⌊ lo g 2 2 M ⌋ , M ∈ Z +
The inner sum is evaluated using the same method used in the original solution. Evaluating the inner sum, we get,
S = ( k = 0 ∑ M − 1 k ⋅ 2 k ) + M ⟹ 2 S = ( k = 1 ∑ M ( k − 1 ) 2 k ) + 2 M ⟹ S = 2 S − S = ( M − 1 ) 2 M + ( k = 1 ∑ M − 1 ( k − 1 − k ) ⋅ 2 k ) + ( 2 M − M ) ⟹ S = ( M − 1 ) 2 M + M − k = 1 ∑ M − 1 2 k
Using the formula for summation of a finite GP, we get,
S = ( M − 1 ) 2 M + M − ( 2 M − 2 ) = ( M − 2 ) 2 M + M + 2
Now, what we need is S m o d 1 0 0 0 . For smaller values of M , this can be computed easily. But it becomes a problem when we're dealing with large values of M . The main hurdle is to compute 2 M m o d 1 0 0 0 . Once we compute this, it becomes easy to compute the rest using elementary modular arithmetic manipulations. We can formulate the following algorithm that uses Euler's Theorem and Chinese Remainder Theorem for dealing with "large enough" M :
∀ M ≥ 3 , 2 M ≡ { 0 ( m o d 8 ) 2 M m o d ϕ ( 1 2 5 ) ( m o d 1 2 5 ) ≡ { 0 ( m o d 8 ) 2 M m o d 1 0 0 ( m o d 1 2 5 )
Let a = 2 M m o d 1 0 0 ( m o d 1 2 5 ) . Then, by the Chinese Remainder Theorem, our congruence system reduces to,
2 M ≡ 3 7 6 a ( m o d 1 0 0 0 ) ⟹ S ≡ 3 7 6 ( M − 2 ) a + M + 2 ( m o d 1 0 0 0 )
Now, computation of a depends on the value of M and can further be possibly generalized using numerical analysis but I think manual computation of a simply using modular arithmetic manipulations is easy and hence, it doesn't need to be simplified further. So, we present our results as follows:
S m o d 1 0 0 0 = ⎩ ⎪ ⎨ ⎪ ⎧ 1 , M = 1 4 , M = 2 ( 3 7 6 ( M − 2 ) a + M + 2 ) m o d 1 0 0 0 ∀ M ≥ 3
where a = ( 2 M m o d 1 0 0 ) m o d 1 2 5 ∀ M ≥ 3
@Prasun Biswas , we really liked your comment, and have converted it into a solution. If you subscribe to this solution, you will receive notifications about future comments.
The given sum is equal to S = k = 1 ∑ 9 k 2 k + 1 0 = 1 ⋅ 2 1 + 2 ⋅ 2 2 + ⋯ + 9 ⋅ 2 9 + 1 0 .
2 S = 1 ⋅ 2 2 + 2 ⋅ 2 3 + ⋯ + 9 ⋅ 2 1 0 + 2 0 .
Subtract these two equations, to get S = 9 ⋅ 2 1 0 − 2 9 − 2 8 − ⋯ − 2 2 − 2 1 + 1 0 = 8 2 0 4
It would have been better if you clarify how you converted the summation to k = 1 ∑ 9 k 2 k + 1 0 .
We note that:
N = 1 ∑ 2 M ⌊ lo g 2 N ⌋ = ⌊ lo g 2 1 ⌋ + ⌊ lo g 2 2 ⌋ + ⌊ lo g 2 3 ⌋ + ⌊ lo g 2 4 ⌋ + . . . + ⌊ lo g 2 2 M ⌋ = 0 + 1 + 1 + 2 + 2 + 2 + 2 + 8 ( 3 ) + 1 6 ( 4 ) + . . . . . . + 2 M − 2 ( M − 2 ) + 2 M − 1 ( M − 1 ) + M = N = 1 ∑ M − 1 2 N N + M
Let us consider:
N = 1 ∑ M − 1 N x N = N = 1 ∑ M − 1 ( N + 1 ) x N − N = 1 ∑ M − 1 x N = N = 0 ∑ M − 1 ( N + 1 ) x N − 1 − N = 0 ∑ M − 1 x N + 1 = d x d N = 0 ∑ M x N − x − 1 x M − 1 = d x d ( x − 1 x M + 1 − 1 ) − x − 1 x M − 1 = x − 1 ( M + 1 ) x M − ( x − 1 ) 2 x M + 1 − 1 − x − 1 x M − 1
Now let x = 2
⇒ N = 1 ∑ M − 1 N x N = N = 1 ∑ M − 1 2 N N = x − 1 ( M + 1 ) x M − ( x − 1 ) 2 x M + 1 − 1 − x − 1 x M − 1 = ( M + 1 ) 2 M − 2 M + 1 + 1 − 2 M + 1 = ( M + 1 − 2 − 1 ) 2 M + 2 = ( M − 2 ) 2 M + 2
Therefore, N = 1 ∑ 2 M ⌊ lo g 2 N ⌋ = ( M − 2 ) 2 M + M + 2
⇒ N = 1 ∑ 2 1 0 ⌊ lo g 2 N ⌋ = ( 1 0 − 2 ) 2 1 0 + 1 0 + 2 = 8 2 0 4
⇒ ⎝ ⎛ N = 1 ∑ 2 1 0 ⌊ lo g 2 N ⌋ ⎠ ⎞ m o d 1 0 0 0 = 8 2 0 4 m o d 1 0 0 0 = 2 0 4
Problem Loading...
Note Loading...
Set Loading...
Let me do the honor of providing clarification (in response to the Challenge Master note on OP's solution) to this wonderful problem!
By the properties of logarithm and floor function, we have,
⌊ lo g 2 N ⌋ = k ∣ 2 k ≤ N < 2 k + 1 , k ∈ Z 0 + ∀ N ∈ Z +
Hence, the sum can be written compactly using double summation notation. Let the sum be S . Then, we can write S as,
S = ⎝ ⎜ ⎛ k = 0 ∑ 9 j = 2 k ∑ 2 k + 1 − 1 k ⎠ ⎟ ⎞ + ⌊ lo g 2 2 1 0 ⌋
Now, the inner sum has a constant as its general term, so, for the evaluation of inner sum, we simply multiply the constant general term with the number of terms in inner sum. The number of terms in the inner sum is ( 2 k + 1 − 1 ) − 2 k + 1 = 2 k . Hence,
S = ( k = 0 ∑ 9 k ⋅ 2 k ) + 1 0 = ( k = 1 ∑ 9 k ⋅ 2 k ) + 1 0 … ( i )
We can ignore the k = 0 case of the sum since k ⋅ 2 k = 0 for k = 0 . Then,
2 S = ( k = 1 ∑ 1 0 ( k − 1 ) 2 k ) + 2 0 … ( i i )
Subtract equation ( i ) from ( i i ) to get,
S = 9 ⋅ 2 1 0 − ( k = 1 ∑ 9 2 k ) + 1 0 = 8 2 0 4 ≡ 2 0 4 ( m o d 1 0 0 0 )